The Third millenium [videorecording] - Dault, Gary Michael; Garwood, Joseph J.; McGreevy, John; Puncher, Jennifer; Ustinou, Peter Sir (Inside the Vatican, 1993)
A story of the Vatican from the Middle Ages to the present and to the future. It begins with the struggles against Protestants waged by Pope Paul III and the Congregation of Roman Inquisition. Introduces Galileo, the scientific genius forced to recant his beliefs on pain of death. Witness the controversial reconciliation of Mussolini and Pope Pius XI. Finally, meet Pope John Paul II, the Pontiff whose popularity and activism set the stage for the next millenium.